Analysis of the Influence of Family Support and Self-Acceptance on Quality of Life Through Compliance with Routine Hemodialisis Visits at Jakarta Haji Hospital - Moh. Fachrurrozy Basalamah; Intan Silviana; Sandra Dewi (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Quality of life of kidney failure patients is closely related to hemodialysis. However, hemodialysis is not a therapy to cure. Hemodialysis is performed only to maintain the patient's life and well-being until kidney function recovers. This study aims to analyze the influence of family support and self-acceptance on quality of life through compliance with routine hemodialysis visits at Haji Hospital Jakarta. This research is quantitative, with a causal relationship model. This research will be carried out at the Jakarta Haji Hospital. This research will be carried out from October to December 2023, with a sample of 109 respondents using a purposive sampling technique, namely patients aged ≥ 18 years (adults) and who have been undergoing hemodialysis for at least 1 month. Analysis techniques use univariate, bivariate, and multivariate and multiple linear regression. The research results show that there is a significant positive influence between family support and self-acceptance on quality of life through compliance with routine visits as an intervening variable. There is a significant positive influence between family support on quality of life. There is a significant positive influence between self-acceptance on quality of life. There is a significant positive influence between family support on compliance with routine visits. There is a significant positive influence between self-acceptance and compliance with routine visits. There is a significant positive influence between compliance with routine visits on quality of life.